Preparation of hydroxyapatite nanofibers by using ionic liquids as template and application in enhancing hydrogel performance - Ren, Xiuli; Liang, Zepeng; Zhao, Xingjun (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Hydroxyapatite (HAP or HA) nanofibers are very attractive in the field of biomedical engineering. However, templates used for preparing HAP nanofibers are usually hydrophobic molecules, like fatty acids and/or surfactants, which are difficult to remove and potentially toxic. Therefore, it is important to develop a green approach to prepare HAP nanofibers. Methods: Imidazolium-based ionic liquids (ILs) were used as templates to control the crystallization of HAP. The obtained HAP nanofibers were composited into polyvinyl alcohol-sodium alginate (PVA-Alg) hydrogel (HAP@H). The rheological performance, stretching, and compression properties were tested. Scanning electron microscope (SEM), high resolution transmission electron microscope (HRTEM), X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), and differential scanning calorimetry (DSC) were adopted to characterize the morphology, size, crystallographic orientations, and phase of HAP@H. Results: HAP nanofibers with a length of ∼50 μm were harvested. The DSC results proved that water loss temperature increased from 98°C (for pure hydrogel) to 107°C (for HAP@H). Also, HAP@H hydrogel presented much better porous structure, tensile performance, and compressive performance than that of pure hydrogel. Discussion: The morphology, size, and growth direction of HAP could be modulated easily by altering the alkyl chain length of ILs’ cations. This is possibly due to face-specific adsorption of imidazolium moieties on HAP nanocrystals. The enhancing performance of HAP@H is probably due to the composited highly oriented HAP nanofibers.